2016
DOI: 10.1007/s13280-016-0801-x
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive responses of tropical tuna purse-seiners under temporal regulations

Abstract: The failure to achieve fisheries management objectives has been broadly discussed in international meetings. Measuring the effects of fishery regulations is difficult due to the lack of detailed information. The yellowfin tuna fishery in the eastern Pacific Ocean offers an opportunity to evaluate the fishers' responses to temporal regulations. We used data from observers on-board Mexican purse-seine fleet, which is the main fleet fishing on dolphin-associated tuna schools. In 2002, the InterAmerican Tropical T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Furthermore, experienced fishers have valuable empirical knowledge on historical species distribution and abundances, and fishing technology evolution, which can help better characterize long and short-term population changes and effort creep, respectively. This non-official source of information is not only very useful in poorly monitored small scale artisanal fisheries (Johannes, 1998;Saldana-Ruiz et al, 2017;Alfaro-Shigueto et al, 2018;Berkstrom et al, 2019;Hunnam et al, 2021), but also in datarich industrial fisheries with rapid technological shifts and complex fleet tactics (Moreno et al, 2007a;Moreno et al, 2007b;Carruthers and Neis, 2011;Lopez et al, 2014;Macusi et al, 2017;Torres-Irineo et al, 2017). Furthermore, fishers' deep practical understanding of how fishing gear works and interacts with different species, gained through years of conducting fishing operations under varying conditions, is extremely valuable to improve selective fishing gear and practices (Hall, 2007;Jenkins, 2010;Poisson et al, 2014;Da Veiga Malta et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, experienced fishers have valuable empirical knowledge on historical species distribution and abundances, and fishing technology evolution, which can help better characterize long and short-term population changes and effort creep, respectively. This non-official source of information is not only very useful in poorly monitored small scale artisanal fisheries (Johannes, 1998;Saldana-Ruiz et al, 2017;Alfaro-Shigueto et al, 2018;Berkstrom et al, 2019;Hunnam et al, 2021), but also in datarich industrial fisheries with rapid technological shifts and complex fleet tactics (Moreno et al, 2007a;Moreno et al, 2007b;Carruthers and Neis, 2011;Lopez et al, 2014;Macusi et al, 2017;Torres-Irineo et al, 2017). Furthermore, fishers' deep practical understanding of how fishing gear works and interacts with different species, gained through years of conducting fishing operations under varying conditions, is extremely valuable to improve selective fishing gear and practices (Hall, 2007;Jenkins, 2010;Poisson et al, 2014;Da Veiga Malta et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The dynamics of the purse seine tuna fleet in the EPO have been detailed by Sun et al (2016), working on social and environmental factors for the spatiotemporal decision process of the purse seine fishery effort. As part of understanding the fisher behavior and the fisheries dynamics when establishing management regulations, Torres-Irineo et al (2017) found that the Mexican purse seine fishery associated with dolphins decreased their time at ports, increased their fishing sets, and maintained the proportion of successful fishing sets in response to closed seasons. Zhang et al (2021) analyzed the fishing behavior of tuna purse seine vessels spatially based on Automatic Identification System (AIS) data to identify the operating status of tuna purse seiners.…”
Section: Introductionmentioning
confidence: 99%